2013
DOI: 10.1364/oe.21.022410
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon absorption-induced photoacoustic imaging of Rhodamine B dyed polyethylene spheres using a femtosecond laser

Abstract: In the present paper we demonstrate the possibility to image dyed solids, i.e. Rhodamine B dyed polyethylene spheres, by means of two-photon absorption-induced photoacoustic scanning microscopy. A two-photon luminescence image is recorded simultaneously with the photoacoustic image and we show that location and size of the photoacoustic and luminescence image match. In the experiments photoacoustic signals and luminescence signals are generated by pulses from a femtosecond laser. Photoacoustic signals are acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…One possibility for future systems would be to combine optical and optoacoustic systems so as to benefit from both the high resolution of an optical microscope and the larger imaging depth of an optoacoustic system. It has already been shown that optoacoustic microscopy can be integrated into an confocal or multiphoton microscope and deliver complementary contrast [83][84][85], but the full potential of combining the two techniques has not been reached yet.…”
Section: (A) (B) (C) (D)mentioning
confidence: 99%
“…One possibility for future systems would be to combine optical and optoacoustic systems so as to benefit from both the high resolution of an optical microscope and the larger imaging depth of an optoacoustic system. It has already been shown that optoacoustic microscopy can be integrated into an confocal or multiphoton microscope and deliver complementary contrast [83][84][85], but the full potential of combining the two techniques has not been reached yet.…”
Section: (A) (B) (C) (D)mentioning
confidence: 99%
“…combination of photoacoustic imaging with diffuse optical imaging 19 , laser scanning microscopy 20 , multiphoton fluorescence imaging 21,22 , ultrasound imaging 23,24 , and optical coherence tomography 16,[24][25][26][27][28][29] . Recently, we presented a fiber-based ncPAI method 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve deep tissue imaging with a high optical resolution and an improved penetration depth compared with the current MPFM, multi-photon photoacoustic imaging is highly desired [6][7][8][9][10][11]. Similar to MPFM [12,13], the photo-excited acoustic signals should be generated nonlinearly by high-intensity optical fields within the focal volume, so the spatial (E.g.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, although different two-photon photoacoustic detection methods have been proposed, how to efficiently separate the multi-photon-absorption-induced acoustic signals from the single-photon-absorption-induced signals is still a critical issue [6,10,11,14,15], with the fact that the nonlinear signal is several orders of magnitude weaker than its linear counterpart. Furthermore, because the linear signal is generated within the whole light path where the excitation light passing through, it is thus impossible to distinguish whether the signal is generated only inside the focal volume, especially in an unknown material under test with a broadband response.…”
Section: Introductionmentioning
confidence: 99%